FLUORIDE GLASS WITH ALUMINUM NITRIDE FILM AND PRODUCTION THEREOF - KAWAGUCHI TOSHIYASU; OSUGA TAKUO; TADA MASASHI; TAI YOSHIO; SUZUKI KOICHI (1991)
PURPOSE:To improve weather resistance by irradiating the surface of fluoride glass with nitride ions, sputtering Al, allowing the sputtered Al to react with the nitrogen ions and forming an AlN film on the surface of the fluoride glass. CONSTITUTION:ZrF4-based fluoride glass 1 such as 50ZrF4-25BaF2-25NaF or AlF3-based fluoride glass such as AlF3-BaF2-CaF2-YF3 and an Al target 2 are set in a binary sputtering device. This device is evacuated to a prescribed degree of vacuum, voltage is impressed and the surface of the fluoride glass 1 fitted to a glass holding means 5 is irradiated with nitride ions 3. At the same time, the Al target 2 is sputtered by ion beam sputtering and fluoride glass with an AlN film is obtd.